The Influence of Perception of Ease, Usefulness, Enjoyment, and Interaction on User Satisfaction and Purchase Intention Through the Chatbot “Tanya” on the Tokopedia Platform - Raihanatul Jennah; Arif Hartono (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The rapid growth of digital technology has accelerated the use of artificial intelligence in customer service, particularly through chatbots on e-commerce platforms. This study examines the effects of Perceived Ease of Use, Perceived Usefulness, Perceived Enjoyment, and Interaction on user Satisfaction, as well as their influence on Purchase Intention, with a focus on Tokopedia's "TANYA" chatbot. Using a quantitative approach, data were collected via an online survey from 195 users who had interacted with the chatbot and analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that Perceived Ease of Use, Perceived Usefulness, and Interaction significantly and positively affect Satisfaction, while Perceived Enjoyment does not. Furthermore, both Satisfaction and Interaction have a significant impact on Purchase Intention. These findings offer practical insights for enhancing AI-based chatbot strategies to improve user satisfaction and stimulate purchasing behavior in e-commerce settings.